Salicylaldehyde rich leaf essential oil composition of Filipundula vestita from western himalaya of Uttrakhand, India - Joshi, Rakesh Kumar (Vietnam Journal of Science and Technology, 2018)
O-hydroxybenzaldehyde or salicylaldehyde has many applications as an intermediate in chemical industries. Genus Filipendula is a potential source of salicycldehyde. Essential oils are prescribed for a variety of health problems by traditional systems of medicine, all over the world. In present study, leaf essential oil composition of Filipendula vestita Wall.Ex G.Don (Family: Rosaceae) from India was analyzed using gas chromatography (GC-FID) and gas chromatography-mass spectrometry (GC-MS) methods. The volatile extract was dominated by salicylaldehyde 51.5%, methyl salicylate 24.5%, salicylic acid butyl ester 5.70%, carvone 4.30%, santene 3.50%, as major constituents.